Bioetica clinica: un approccio centrato sul rispetto per la dignità del paziente come persona - Viafora, Corrado (Filosofia Morale/Moral Philosophy, 2025)
This essay is inspired by the insights gained in over three decades of engagement within clinical contexts. Not only has such engagement been particularly significant to understand the moral experience embedded within clinical practice, but it has also been instrumental in shaping a bioethical approach capable of interpreting that moral experience. A first, fundamental insight is that, in view of the radical challenges currently moved against the constitutive aims of clinical practice, we need to interpret them in the light of an ethical principle that is also functional for clinical practice. This principle could be the idea of human dignity, shaped in terms of respect for the patient as a person. Within this perspective, particular emphasis is placed on the distinction between recognising every patient as a person, with a commitment to respecting her dignity, and justifying what this recognition entails in specific clinical contexts. This underscores the need for an argumentative framework that leverages the idea of human dignity to justify ethical judgments in the highly sensitive domain of clinical practice. The essay aims to explain the rationale behind this framework and the stages through which it develops. As contemporary clinical practice increasingly faces problems of a distinctly ethical nature, requiring the application of the inherent logic of moral reasoning, the importance of fostering a genuine ethical-argumentative mindset among health professionals emerges as the central goal of the “critical companionship” offered by a philosophically oriented clinical bioethics.